Prostaglandin E(2) Mediates Immunosuppression in Acutely Decompensated Cirrhosis - O’Brien, Alastair J. (Nat Med, 2014)
Patients with advanced cirrhosis experience frequent infections leading to sepsis, which carries high mortality. While innate immune dysfunction underlies this vulnerability, the precise cause remains elusive. We found prostaglandin (PGE(2)) elevated in acutely decompensated (AD) patients at immunosuppressive levels. Plasma from AD and end-stage liver disease (ESLD) patients suppressed macrophage cytokine secretion and bacteria killing in a PGE(2) receptor-dependent manner, effects not seen in stable cirrhosis. Mouse models (bile duct ligation and CCL4-liver injury) also demonstrated elevated PGE(2), which when inhibited completely restored immune competence and survival following infection. Importantly, albumin binds/inactivates PGE(2) resulting in greater PGE(2) bioavailability. This results in enhanced immunosuppressive effects of AD plasma in patients with low albumin levels. Administering albumin to AD patients reversed immunosuppressive properties of their plasma; protective effects recapitulated in rodent survival studies. Thus, elevated PGE(2) combined with hypoalbuminemia mediates immunosuppression in AD and ESLD patients, which can be reversed with albumin.